Hedonisme Perempuan Urban Karir dalam Novel Metropop Critical Eleven Karya Ika Natassa - Afifah Chairunnisa; Hasanuddin WS (Persona: Kajian Bahasa dan Sastra, 2023)
This article aims to explain and describe the hedonism of career women in the metropop novel entitled Critical Eleven by Ika Natassa. This is descriptive qualitative research with an ethnographic approach. There are 4 hedonim of career women found by researchers, including (1) consumptive lifestyles, this could be seen in their behavior such as like to buy expensive and luxury goods, use public transportation, eat relatively expensive fast food, make discretionary purchases, and hire domestic helpers. (2) the lifestyle industries and social classes, as can be seen in their behavior such as they attach great importance to or attention to appearance. (3) chatting/gathering/joining, including hanging out in cafes or restaurants and watching movies with friends or family. (4) the lifestyle mobilities, including working out-of-town or abroad, migration, and leaving their social status (occupations) very often.